2002
DOI: 10.1128/aac.46.5.1510-1515.2002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Interactions of Artemisinin with Atovaquone, Quinine, and Mefloquine againstPlasmodium falciparum

Abstract: The interactions of artemisinin with atovaquone, quinine, and mefloquine were investigated in three Plasmodium falciparum strains (strains F-32, FCR-3, and K-1) by an in vitro culture assay. The parasites were cultured for 48 h in the presence of different concentrations and proportions of two drugs at a time in a checkerboard design. The response parameters were determined, and the sums of the fractional inhibitory concentrations (⌺FICs) of the drug combinations were calculated for different degrees of inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 23 publications
(23 reference statements)
2
38
0
3
Order By: Relevance
“…This suggests that at high concentrations ATV could have an alternative mode of action against resistant parasites compared to its mode of action at lower concentrations lethal to ATV-sensitive parasites. Using the checkerboard technique, Gupta et al (11) reported an indifferent interaction and a synergistic interaction (obtained from IC 50 s and IC 90 s, respectively) between artemisinin and ATV in ATV-sensitive parasite lines. Although the investigators claimed an indifferent interaction, all the points on the isobologram lay above the line of indifference, which would be consistent with our results and those of Canfield et al (2).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that at high concentrations ATV could have an alternative mode of action against resistant parasites compared to its mode of action at lower concentrations lethal to ATV-sensitive parasites. Using the checkerboard technique, Gupta et al (11) reported an indifferent interaction and a synergistic interaction (obtained from IC 50 s and IC 90 s, respectively) between artemisinin and ATV in ATV-sensitive parasite lines. Although the investigators claimed an indifferent interaction, all the points on the isobologram lay above the line of indifference, which would be consistent with our results and those of Canfield et al (2).…”
Section: Discussionmentioning
confidence: 99%
“…In this system: SFIC < 1 denotes synergism, 1 < SFIC < 2 denotes additive interaction, while SFIC ≥ 2 denotes antagonism (Gupta et al, 2002).…”
Section: In Vitro Drug Interaction Experimentsmentioning
confidence: 99%
“…The sum FIC (ΣFIC) value for each of the six combinations was determined to classify the drug-drug interaction [16][17][18] as ΣFIC=FIC (artemisinin)+FIC (amphotericin B) or FIC (miltefosine) where ΣFIC <1 represented synergism, ΣFIC ≥1, but <2 represented additive interaction and ΣFIC ≥2 indicated antagonism.…”
Section: Preparation Of Isobologrammentioning
confidence: 99%